MENINGKATKAN HASIL BELAJAR KIDS ATLETIK LEMPAR TURBO MELALUI MODIFIKASI PERMAINAN BOLA BEREKOR BAGI SISWA KELAS 5 SDN 1 SUKOREJO TAHUN AJARAN 2013/2014 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the improvement of learning outcomes athletic kids throwing turbo through modification of the game ball tailed for the Grade 5 Elementary School 1 Sukorejo academic year 2013/2014 . This study uses action research. In the implementation consists of two cycles. The instrument used in this study is the test performance of students, student observation sheet, and a written test. Based on the results, the percentage of mastery learning in the first cycle, psychomotor aspects of 32.4 %, 76.5 % affective aspects, cognitive aspects of 94.2 %, and mastery learning students classically 64.7 % of the total number of students. In the second cycle psychomotor aspects of 76.5 %, 88.2 % affective aspects, cognitive aspects of 97.1 %, and mastery learning students classically 85.3 % of the total number of students. In the present study showed an increase in student learning in classical completeness by 20.6 %, from 64.7 % to the first cycle to 85.3 % in the second cycle. Based on the above results, it was concluded that the modification of the game ball tailed in teaching athletic kids throwing turbo can improve student learning outcomes the Grade 5 Elementary School 1 Sukorejo academic year 2013/2014.